Analisis Pengaruh Penambahan Aditif Xanthan Gum Pada Lumpur Pemboran - Darmiyati, Zela Madani; Randanan, Eltimeyansi Chrisye; Sulardi; Wicaksono, R. Bambang; Aditya, Rifki; Darmiyati, Iin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
This study investigated the use of Xanthan gum as an additive to improve the rheology of drilling mud. The parameters used in this rheology are viscosity, yield point, shear stress, and gel strength. This experiment was conducted in the laboratory to evaluate the effects of bentonite, fresh water, and Xanthan gum additives at various concentrations. During the experiment, five drilling mud samples containing 1, 3, 5, 7, and 15 grams of Xanthan gum were prepared. In the sample containing 1 gram of Xanthan gum, the viscosity was measured for 120 seconds/quarter, the yield point was found to be 24 lb/100ft², the plastic viscosity was found to be 4 cp, and the gel strength was found to be 0.78 lb/100ft². Meanwhile, the sample containing 15 grams of Xanthan gum has a viscosity of 4800 seconds/quarter, a plastic viscosity of 20 cp, a yield point of 52 lb/100ft², and a gel strength of 1.3 lb/100ft². The final result shows that the increase in the rheological properties of the mud is due to Xanthan gum which is in accordance with API standard drilling.